2015
DOI: 10.1027/2151-2604/a000208
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory and Number Sense as Predictors of Mathematical (Dis-)Ability

Abstract: Recent research has pointed to two possible causes of mathematical (dis-)ability: working memory and number sense, although only few studies have compared the relations between working memory and mathematics and between number sense and mathematics. In this study, both constructs were studied in relation to mathematics in general, and to mathematical learning disabilities (MLD) in particular. The sample consisted of 154 children aged between 6 and 10 years, including 26 children with MLD. Children performing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
41
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 38 publications
12
41
6
1
Order By: Relevance
“…Following this viewpoint, it could be concluded that part of the MLD children, the ones with the more serious problems, probably have number sense deficits, while the math learning difficulties of the other children with learning difficulties could be attributed to other causes (such as working memory). Other studies, however, found that children with deficits in number sense have comparable math scores as children with deficits in working memory, but that children with deficits in both number sense and working memory have the lowest math scores (Kroesbergen & Van Dijk, 2015;Toll et al, 2016). This supports the view that number sense deficits can explain MLD, but that other factors are important too.…”
Section: Number Sensesupporting
confidence: 72%
See 4 more Smart Citations
“…Following this viewpoint, it could be concluded that part of the MLD children, the ones with the more serious problems, probably have number sense deficits, while the math learning difficulties of the other children with learning difficulties could be attributed to other causes (such as working memory). Other studies, however, found that children with deficits in number sense have comparable math scores as children with deficits in working memory, but that children with deficits in both number sense and working memory have the lowest math scores (Kroesbergen & Van Dijk, 2015;Toll et al, 2016). This supports the view that number sense deficits can explain MLD, but that other factors are important too.…”
Section: Number Sensesupporting
confidence: 72%
“…Many studies have shown that children with MLD in general have lower working memory skills than TD children (e.g., Geary, Bailey, & Hoard, 2009;Geary et al, 2007;Raghubar et al, 2010;Schuchardt et al, 2008). It has also been found that children with low working memory skills have low mathematical abilities (e.g., Alloway, Gathercole, Kirkwood, & Elliott, 2008;Kroesbergen & Van Dijk, 2015). Especially visual spatial working memory seems to be impaired in children with MLD (Ashkenazi, Rosenberg-Lee, Metcalfe, Swigart, & Menon, 2013;Szucs, Devine, Soltesz, Nobes, & Gabriel, 2013).…”
Section: Working Memorymentioning
confidence: 97%
See 3 more Smart Citations